2017
DOI: 10.1007/s00256-017-2645-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast-enhanced MR imaging in osteoid osteoma: relationships with clinical and CT characteristics

Abstract: This study suggests more abundant vascularization of OOs with long-lasting pain and location on short or flat bones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…7) [49]. Pottecher et al used a variable time resolution and suggested that to eliminate the Nyquist limit, a temporal resolution of 3 s would be required [28]. These observations also support the use of angiographic imaging on 4D MRI [50].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 81%
See 4 more Smart Citations
“…7) [49]. Pottecher et al used a variable time resolution and suggested that to eliminate the Nyquist limit, a temporal resolution of 3 s would be required [28]. These observations also support the use of angiographic imaging on 4D MRI [50].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 81%
“…Using sequences repeated every 30 s after the administration of gadolinium, Liu et al showed that OOs exhibit a peak in signal enhancement during the arterial phase in 82% of the cases [44]. Several subsequent studies confirmed that this enhancement pattern was present in 82 to 100% of OOs using temporal resolutions that varied between 12 and 30 s [28,[45][46][47][48]. Some authors used a higher temporal resolution (sequences repeated every 3 s) and demonstrated that an enhancement delay of less than 6 s between the lesion and an adjacent artery was also a typical characteristic of OO ( Fig.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
See 3 more Smart Citations